Utilization of Gunungkidul Zeolite Stone as a Catalytic Converter in Motorcycle - Triwibowo, Nur Akhmad; Novianto, Thomas; Budiono, Cyrilus Sukaca (Institut Teknologi Dirgantara Adisutjipto, 2018)
One way to reduce the level of exhaust emissions is catalytic converter addition in the exhaust gas. The alternative material for catalytic converters is zeolite stone which is local material that is widely available in Gunungkidul Regency. This study aims to determine the effect of Gunungkidul zeolite catalytic converters on the absorption of motorbike engine exhaust emission. The side effects of motorbike performance is also evaluated. The results showed that the use of zeolite Gunungkidul stone as a catalytic converter can absorb CO (9,5% - 21,6%) and HC gases (15,5% - 63,9%) quite well and can meet the quality standards of motorcycle exhaust emissions but has side effects to reduce engine performance even though the decrease is relatively small (5%).